Comparative company law : text and cases on the laws governing corporations in Germany, the UK and the USA - Cahn, Andreas; Donald, David C., 1958- (Cambridge, United Kingdom : Cambridge University Press, 2018)
'Chapters open with discursive analyses of the law in each of Germany, the UK and the US (Delaware, the ABA Model Business Corporation Act, and federal securities laws) and set out the high-level governing framework, particularly for the EU and its member states'--
Includes bibliographical references and index.
Keywords: Corporation law -- United Kingdom; Corporation law -- United States; Corporation law -- Germany